THE NEXUS OF INTERNATIONAL MARKETING MANAGEMENT AND SUSTAINABLE TOURISM IN THE DIGITAL ERA: A BIBLIOMETRIC REVIEW - SURYAWAN, TJOKORDA GDE AGUNG WIJAYA KESUMA (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
In an era defined by rapid technological advancements and growing sustainability concerns, understanding the intersection of international marketing and tourism is crucial. This bibliometric analysis comprehensively explores the evolving nexus of international marketing management, sustainable tourism, and digital technologies. Utilising a meticulously curated dataset of 398 peer-reviewed articles, this study maps the field's intellectual structure, identifies key thematic clusters, and illuminates emerging research frontiers. The review synthesises how digital tools, including immersive technologies and social media, strategically promote sustainable tourism and enhance visitor experiences, whilst addressing challenges like overtourism and cultural preservation. Findings reveal significant publication growth since 2012, reflecting robust multidisciplinary engagement. Four distinct clusters emerged: Digital Marketing Strategies for Sustainable Tourism; Immersive Technologies and Visitor Experience Enhancement; Sustainable Tourism Development and Management; and Museums as Hubs for Cultural Sustainability and Engagement. The analysis underscores the field’s interdisciplinary character, the centrality of value co-creation, and the growing emphasis on resilience and digital transformation. This study offers a structured, data-driven foundation for future scholarly inquiry and provides valuable insights to inform strategic decision-making within the dynamic global tourism industry.